Delayed repair of aortic dissection in sickle cell anaemia as a combined cardiac and vascular surgical approach - Capoccia, Massimo (J Saudi Heart Assoc, 2020)
We discuss a patient who presented with a type B aortic dissection with a retrograde progression in the context of sickle cell anaemia. Given the involvement of the superior mesenteric artery and concern for bowel ischaemia, a delayed approach was considered. Subsequently, a frozen elephant trunk was performed in the hybrid theatre with the back-up of the vascular surgeon for mesenteric protection. A technically demanding procedure followed by a prolonged and challenging postoperative course finally led to a successful outcome. We argue that the case presented is an example of how a close cooperation between professionals can offer additional options to treatment based on a mixture of skills and background to achieve the desired outcome.